Non cooperative fuzzy games in normal form: a survey - Larbani, Moussa (Elsevier BV, 2009)
In this paper, we present a review of most of the approaches for solving non-cooperative fuzzy games in normal form. Applications of these games are reviewed as well. We also present a new class of fuzzy games in normal form: the class of non-cooperative games involving fuzzy parameters. Finally, some potential directions of research are provided throughout the paper and in the conclusion